An automated statis perimeter/adaptometer using light emitting diodes. Issue 7 (July 1983) - Ernst, W.; Faulkner, D. J.; Hogg, C. R.; Powell, D. J.; Arden, G. B.; Vaegan,
Abstract : An automated static perimeter/adaptometer is described which measures thresholds with lights of 2 wavelengths. The instrument uses light-emitting diodes to produce the stimuli and is controlled by a small computer, making it very suitable for clinical testing of large numbers of patients. The use of 2 LEDs with different peak emission wavelengths (530 and 660 nm) permits an assessment of the relative state of rod and cone mechanisms in a particular region of the retina either during dark adaptation or when the eye is fully dark adapted.